The meme as the message - Nowotny, Joanna, author.
1 online resource
Keywords: This book sheds light on the phenomenon of memes, covering everything from pandemic humour to far-right propaganda, from feminist memes to algorithmic censorship. Memes are far more than light entertainment - they are complex cultural artefacts that play a role in politics, in art, and in platform economics.Taking a cultural studies perspective, the authors analyse individual memes in entertaining case studies, systematising their findings in order to redefine this digital form of communication. Chapters connect memes with other digital phenomena such as trolling, and combine extensive close readings of exemplary individual memes with regards to form and aesthetics with an acute awareness of power dynamics and other context phenomena surrounding memes. The book develops an innovative theoretical approach that presents the term "memesis" to capture the very specific quality of meme production and reception as a form of collective creative rewriting of a template in accordance with algorithmic logic.Offering an important contribution not only to the still young field of meme studies but also to the general negotiations of questions around digital literacy, this book will interest not only scholars and students of digital media, visual communication, cultural studies, and media and politics but anyone with a keen interest in digital culture - and how it shapes our lives.